2012
DOI: 10.1002/dev.21086
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vitamin D3 during pregnancy and lactation on offspring physiology and behavior in Sprague–Dawley rats

Abstract: Recent findings show that developmental vitamin D deficiency leads to altered brain morphology and behavioral development in the rat offspring. We examined the effects of different dietary vitamin D levels in rat dams on behavior and biochemistry of the offspring. Females were divided into five conditions and received diets containing 0, 1,5, 3.3, 6.0, or 10.0 IU/g of vitamin D₃ from mating to weaning. Offspring were tested as juveniles and as adults for anxiety, social learning and behavior, and locomotion. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Although sunlight-induced vitamin D is not an important source of vitamin D for lower animals, it has been shown that prenatal dietary vitamin D in Sprague-Dawley rats has significant effects on postnatal anxiety and social behaviors (Pan et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Although sunlight-induced vitamin D is not an important source of vitamin D for lower animals, it has been shown that prenatal dietary vitamin D in Sprague-Dawley rats has significant effects on postnatal anxiety and social behaviors (Pan et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Juvenile progeny of VDD Sprague-Dawley rat dams treated from mating until weaning showed heightened anxiety-like behaviors, as measured by significantly increased grooming frequency compared to other groups when tested in the elevated plus maze (EPM, measures anxiety-like and exploratory behaviors) (Pan et al 2014). Interestingly, juvenile offspring of dams provided an excessive vitamin D diet (10.0 IU/g) also showed significantly increased grooming frequency during social behavior and learning tests (Pan et al 2014). Effects of maternal VDD on anxiety-related behavior appear to be independent of the hypothalamic-pituitary-axis (HPA) with one study showing normal function in rats born to VDD dams (Eyles et al 2006).…”
Section: Neuro-affective Disordersmentioning
confidence: 99%
“…For instance, U- and J-shaped associations between 25(OH)D concentration and disease outcomes have been previously reported [ 27 , 28 , 29 ] and could also exist in relation to neurodevelopment and maternal vitamin D status. Adverse effects of elevated 25(OH)D concentration on both offspring behavior and physiology have been observed in animal models [ 30 ] but it is unknown on how translatable this is to humans.…”
Section: Introductionmentioning
confidence: 99%